Desain Rusunawa Meulaboh Smart Building (MSB) Menggunakan Special Moment Resisting Frame System (SMRFS) - Rahman, Aulia; Opirina, Lissa; Agusmaniza, Roni; Zulfrizal, M. (VOCATECH: Vocational Education and Technology Journal, 2024)
AbstractThe earthquake that hit Aceh on December 26, 2004 caused severe damage to various facilities, physical infrastructure, including buildings. To overcome damage to buildings due to earthquakes, it is by designing building structures using the Special Moment Resisting Frame System (SMRFS). The purpose of this study is to determine the dimensions of effective cross-section, repetition and structural performance against earthquake loads using SMRFS. The analysis method in this study uses  ETABS V.21 Software to determine the capacity of the building after using the Special Moment Resisting Frame System (SMRFS), planning is carried out in the city of Meulaboh where the SDS value is 0.8910 and SD1 0.6800 are included in the seismic design category D. The results of the analysis show that the cross-sectional dimensions of the structure have met the cross-sectional criteria for SMRFS, the requirements of strong columns are met. The inter-floor gap is smaller than the permit intersection, the largest intersection on the 7th floor with a ∆ value of 43.9140 mm is smaller than ∆a 88 mm. The repetition ratio of beams, columns and plates meets the repetition requirements for which ρbeam has been obtained. Based on the results obtained, the dimensions of the structural components are included in the most effective, namely the size of B1 600/400 mm, B2 600/350 mm, K1 500/450 mm, plate 150 mm and plate 120 mm because the fundamental period includes the maximum where T = 0.8150 seconds does not cross the lower limit Ta (min) = 0.8291 seconds and the upper limit Ta (max) = 1.1607 seconds. By complying with the shear capacity (VT) design requirements, the columns and beams are designed to reduce shear forces due to earthquakes. The dimensions of the structural components of each floor must also conform to the design criteria of reinforced concrete, and the nominal shear capacity (VT) must be greater than the force acting on the columns and beams (V). AbstrakGempa bumi yang melanda Aceh pada 26 desember 2004 menyebabkan kerusakan parah pada berbagai sarana, prasarana fisik, termasuk bangunan. Untuk mengatasi kerusakan pada bangunan akibat gempa yaitu dengan mendesain struktur bangunan menggunakan Special Moment Resisting Frame System (SMRFS). Tujuan penelitian ini untuk mengetahui dimensi penampang efektif, penulangan dan kinerja struktur terhadap beban gempa yang menggunakan SMRFS. Metode analisis pada penelitian ini menggunakan Software ETABS V.21 untuk mengetahui kapasitas gedung setelah digunakan Special Moment Resisting Frame System (SMRFS), perencanaan dilakukan dikota meulaboh dimana nilai SDS 0.8910 dan SD1 0.6800 termasuk kategori desain seismik D. Hasil analisis menunjukkan dimensi penampang struktur memenuhi kriteria penampang untuk SMRFS, syarat kolom kuat terpenuhi. Simpangan antar lantai lebih kecil dari simpangan izin, simpangan paling besar di lantai 7 yaitu ∆ 43.9140 mm lebih kecil dari ∆a 88 mm. Nilai rasio penulangan balok, kolom dan plat memenuhi syarat penulangan dimana ρbalok dibawah ρbalok ijin. Berdasarkan hasil diperoleh dimensi bagian struktur sudah termasuk yang paling efektif yaitu ukuran B1 400/600 mm, B2 350/600 mm, K1 450/500 mm, plat 150 mm dan plat 120 mm disebabkan oleh periode fundamental paling besar T = 0.8150 detik tidak melewati batas bawah Ta (min) = 0.8291 detik dan batas atas Ta (max) = 1.1607 detik. Struktur mematuhi syarat desain kapasitas geser (VT), kolom dan balok yang didesain dapat mengurangi gaya geser akibat gempa. Dimensi komponen struktur setiap lantai juga harus sesuai kriteria desain beton bertulang, dan kapasitas geser nominal (VT) harus lebih besar dari gaya yang bekerja pada kolom dan balok (V).